Flows along arch filaments observed in the GRIS 'very fast spectroscopic mode'. Issue Volume 12:Issue S327(2016) (12th September 2017) - Manrique, S. J. González; Denker, C.; Kuckein, C.; Yabar, A. Pastor; Collados, M.; Verma, M.; Balthasar, H.; Diercke, A.; Fischer, C. E.; Gömöry, P.; González, N. Bello; Schlichenmaier, R.; et al.
Abstract: A new generation of solar instruments provides improved spectral, spatial, and temporal resolution, thus facilitating a better understanding of dynamic processes on the Sun. High-resolution observations often reveal multiple-component spectral line profiles, e.g., in the near-infrared He i 10830 Å triplet, which provides information about the chromospheric velocity and magnetic fine structure. We observed an emerging flux region, including two small pores and an arch filament system, on 2015 April 17 with the 'very fast spectroscopic mode' of the GREGOR Infrared Spectrograph (GRIS) situated at the 1.5-meter GREGOR solar telescope at Observatorio del Teide, Tenerife, Spain. We discuss this method of obtaining fast (one per minute) spectral scans of the solar surface and its potential to follow dynamic processes on the Sun. We demonstrate the performance of the 'very fast spectroscopic mode' by tracking chromospheric high-velocity features in the arch filament system.